N-Back Task Training Helps to Improve Post-error Performance - Li, Qing; Long, Quanshan; Hu, Na; Tang, Yancheng; Chen, Antao (Frontiers in Psychology, 2020)
Improved performance on working memory (WM) through training has been widely expected to transfer to other domains. Recent studies have proposed that WM training could enhance the autonomous coordination of WM processes. Based on the shared processes between WM and error processing, our present study explored the transfer effect of 15 days training on post-error performance during the n-back task compared to a simple visual search task. Participants were randomly assigned to either the training (N = 22) or control (N = 18) group. We found that WM training successfully improved WM performance. After training, compared with the control group, the training group showed a significant reduction in post-error slowing (PES); however, post-error accuracy and the flanker effect were not modulated by WM training. Moreover, we observed a significant, negative correlation between the changes in PES and WM from pretest to posttest and classified two groups based on these changes in PES with 70% accuracy. Thus, in our present sample, WM training improved post-error performance. We propose that the skill of controlling information flow developed during WM training is transferable to other tasks and discuss the implications of current findings for understanding the generation of PES.